If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2m+2-3=0
We simplify the equation to the form, which is simple to understand
2m+2-3=0
We move all terms containing m to the left and all other terms to the right.
+2m=0-2+3
We simplify left and right side of the equation.
+2m=+1
We divide both sides of the equation by 2 to get m.
m=0.5
| -3(y-17)=12 | | 18=-4+4 | | -6(-3+8n)=210 | | 3w+(-7)=19+w | | 5x-3y=-1 | | F-63=937 | | a^2+11a+18=1 | | -5n+2n= | | -8-x=x-4r | | 4/31x+8/31=16/31 | | P+1.5=1.5 | | 5(c+4/5)+6=-20 | | 14=7(x-6) | | X/-3+2=9+x | | y=3x-34 | | -1/3(12+9y)=4-3y | | 2/3+1/4t=2 | | y-3=3y-43 | | 7(x-3)+8=2(x-4) | | X/3+2=9+x | | 1-.75x-4x=39 | | 2x=43 | | X+6=.5(12+2x) | | 2(2x-3)=(-1)-x | | 22-83= | | 9n^2-2n-41=0 | | -8x+12=2x+11 | | 2r-6=26 | | 22/2+17= | | 1/2(6-x)+3x=1/2x-8 | | -2x^6-16x^5-32x^4= | | -10=-2x+.33x+5 |